Contributions Of International, Regional, National, Local Feminists And Women Organisation Networks To Women Development - Afolabi, Comfort Yemisi (Advances in Social Sciences Research Journal, 2020)
The sufferings of women in the society and other acts of discrimination against women resulted in the rise of women or feminist movements worldwide especially in the Northern countries of the globe. As a result of the dehumanization of women in most communities of the world, many activists and women movements evolved to proffer solutions to women and gender issues. This paper examined the contributions of international, regional, national and local women’s movements to development. The paper delved into the Waves of Feminism which made various changes and resulted in major freedom and development for women in education, family life, health wise, employment and politics. It looked at the importance of women to economic development. Various women’s movements and networks were discussed. Challenges of these women’s movements were identified and recommendations were made. The paper employed secondary sources for information for the study.